Language, Paralanguage and Kinesics in Korean Communication: A Tripartite Analytical Framework - Benjamin-Ohwodede, Jacinta (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
ABSTRACTThis study looks at how language, paralanguage and kinesics work together in Korean communication. It shows that meaning is often indirect and depends on the situation. Ferdinand Poyatos’ tripartite framework of language, paralanguage and kinesics is used to evaluate Korean interactions. This study uses a qualitative technique to examine how these communication cues function in many social and cultural situations. The results suggest that meaning in Korean communication is not only derived from language but also from the combination of verbal and nonverbal cues. The study concludes that language and non-linguistic signs work together in Korean communication, which is a multimodal and culturally ingrained system that should not be studied separately.